Religiosity As Protection Against The Acceptance Of Rape Myths Among Students At Islamic Universities - Mundzir, Ilham; Razak, Yusron; Nur Peni, Wike; Muthmainnah, Yulianti; Pao, Chai (Al Irsyad: Jurnal Studi Islam, 2026)
Limited empirical evidence exists on the relationship between religiosity and acceptance of rape among Islamic university students in Indonesia. This study aims to analyze the relationship between religiosity and acceptance of rape and understand students’ perceptions of sexual violence. This study used an explanatory sequential mixed-method design at two Islamic universities. Quantitative correlational analysis (N=162) with MUDRAS and SRMA scales was followed by qualitative case study interviews analyzed thematically. Quantitative results show no significant relationship between religiosity and acceptance of rape, with a very weak positive correlation (r = 0.049, p = 0.532). This indicates that higher religiosity does not necessarily reduce acceptance of rape myths. Qualitative findings reveal that students generally demonstrate strong awareness of sexual violence issues, rejecting victim blaming, consent misinterpretation, and rape myths. Despite high levels of religious practice and moral self-control, these factors do not translate into statistically significant attitudes toward rape myth rejection. The findings highlight a disconnect between religiosity and attitudes toward sexual violence, suggesting the influence of broader social and cultural factors beyond religion alone. Religiosity is not significantly related to acceptance of rape among Islamic university students in this study context. Findings inform educational and policy strategies emphasizing multidimensional approaches beyond religiosity to prevent sexual violence effectively in society.